2017
DOI: 10.18203/2394-6040.ijcmph20175355
|View full text |Cite
|
Sign up to set email alerts
|

Oral cancer and tobacco: a case control study in southern India

Abstract: Background: Cancer is one of the major threats to public health in the developed world and increasingly in the developing world. In India, oral cancer is the leading cancer in males and ranking third in females. The risk factors for the development of oral cancers include tobacco smoking.Methods: A Case control study done at Kidwai Memorial Institute of Oncology, Bangalore, India. Study subjects included histological confirmed new cases of oral cancer attending the hospital during the period of April 2014- May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
1
0
0
Order By: Relevance
“…Oral cancer is a chronic disease. Our study showed most common presentation in the age group of 51-60 years that comprised 44% of cases, hence our study was consistent with the research done by Nirmala et al 10 who showed that 39% belonged to the age group of 50-59 years and Tandon et al also showed that 39.5% 11 were patients above 50 years old. However, our study was contradictory to the previous study done by Singh et al 8 where the majority of patients were in the age group of 40-49 (25.2%), and Smitha et al also showed that the majority belonged to 60 years (33.9%).…”
Section: Discussionsupporting
confidence: 92%
“…Oral cancer is a chronic disease. Our study showed most common presentation in the age group of 51-60 years that comprised 44% of cases, hence our study was consistent with the research done by Nirmala et al 10 who showed that 39% belonged to the age group of 50-59 years and Tandon et al also showed that 39.5% 11 were patients above 50 years old. However, our study was contradictory to the previous study done by Singh et al 8 where the majority of patients were in the age group of 40-49 (25.2%), and Smitha et al also showed that the majority belonged to 60 years (33.9%).…”
Section: Discussionsupporting
confidence: 92%